Aplicación de los principios, criterios e indicadores del FSC (Consejo de Administración Forestal) para la certificación de una unidad de manejo forestal en el Cantón Ventanas, Provincia de Los Ríos, año 2019. - Osorio Aldaz, Carlos Adrián (2019)
The present investigation was carried out in the hacienda "Rafaelita" located in the canton of Ventanas in the province of Los Ríos. The objectives of the investigation were; improve and ensure the good management of the forest unit applying the principles, criteria and indicators of the FSC. To do this, the analytical - evaluative method was implemented in the methodology, since in order to obtain or apply for the FSC certification, the work that must be done must be planned in advance. Here the 10 principles of the FSC were applied, with their respective criteria and indicators and the application of these principles will be made according to each indicator in the management unit, information was obtained associated with the FSC standards, and manuals were prepared by writing the procedure that must be met by each person who will work in the UMF. The result of the research was that of the 10 FSC principles, only seven principles could be applied, because principles 3.5 and 9 are not applicable within the UMF, because it is a plantation and not a forest. and that there is no indigenous settlement, nor areas of archaeological interest, the other principles were applied without any type of inconvenience, obtaining all the documentation requested by the FSC and developing the management plan with their respective schedules and work manuals to obtain the certification in the UMF. Keywords: Certification, FSC, forest management unit.